Analysis of Immune Microenvironment by Multiplex Immunohistochemistry Staining in Different Oral Diseases and Oral Squamous Cell Carcinoma - Qiao, Bin; Huang, Junwen; Mei, Zi; Lam, Alfred King-yin; Zhao, Junfang; Ying, Le (Frontiers in Oncology, 2020)
Purpose: The aim is to investigate the impacts of using multiplex immunochemistry (mIHC) staining to analyses the co-expression of PD-L1 and TILS (CD8+ T cells and FOXP3+ regulatory T cells (Tregs)) in different oral diseases, and oral squamous cell carcinoma (OSCC). Methods: Formalin fixed paraffin-embedded tissue sections from different oral diseases were stained with PD-L1 and TILs (CD8+ T cells and FOXP3+ Tregs) by mIHC staining simultaneously. The whole slide was scanned digitally to observe the cell phenotypes stained in the microenvironment. The contents of each slice were read using a computer-aided method to analyse and the cell densities were calculated using statistical software. Results: We were able to characterize the tumour microenvironment (TME) of different oral diseases including oral leukoplakia, inflammatory gingiva, oral lichen planus and SCC, with accurate visualization of various immune cells harbouring complex immune phenotypes by mIHC staining. The results showed that PD-L1 was up-regulated in SCC tissues at different pathological stages, while CD8 and FOXP3 had no significant changes. The ratio of PD-L1/CD8 was also significantly up-regulated in SCC tissues compared with that of other oral diseases. In advanced stages of OSCC, the FOXP3/CD8 ratio increased, and immunosuppressive TME was more pronounced. In addition, we also found different immune phenotypes: the inflamed phenotype, immune-excluded phenotypes and immune-desert phenotypes. By locating tumour epithelial cells, we found that PD-L1 expression is in both tumour cells and stromal cells. Conclusions: mIHC is useful for the visualization and evaluation of tumour microenvironment in immuno-oncology research. It allows single-cell imaging in situ and could effectively and quickly determine the immune phenotype of different oral diseases.